(untitled) (Baltic Journal of Sport and Health Sciences, 2012)
Research background and hypothesis. Over the last years, basic research on the effect of different hormones on tendons and ligaments has been initiated. Regarding oestrogen receptor localization in brain and their interaction with neurotransmitters (Maki et al., 2002; Friden et al., 2003; Farage et al., 2008), we speculate that the increase in the level of female sex hormone concentration will improve the sense of movement. Research aim was to study the effect of increased female sex hormone concentration on movement proprioception. Research methods. Subjects were healthy and physically active women (n = 15) with normal menstrual cycle, aged 19–23 years, body weight – 58.2 ± 6.1 kg, height – 168.4 ± 5.6 cm as well as female basketball players (n = 15) with normal menstrual cycle, aged 19–23 years, body weight – 78.31 ± 2.81 kg, height – 182.40 ± 4.71 cm. We performed three experiments with each participant: in follicular phase, ovulation and luteal phase. The samples of 5 ml venom blood were taken to establish the amount of estradio17β-estradiol and progesterone concentration. The sense of knee joint position was evaluated using isokinetic dynamometer (System 3; Biodex Medical Systems, Shirley, New York, USA). During a training session, a subject’s right leg was flexed at the knee joint and fixed at the angle of 90°. Prior to each test, the researcher demonstrated the target angle of 60° by stretching subject’s leg. In order to train the flexion of the knee joint, a subject’s right leg was extended at the knee joint and fixed at the angle of 0°. The researcher demonstrated the target angle of 50° by flexing subject’s leg. The subjects had to perform three tests at the velocity of 2°/s, 5°/s and 10°/s with their eyes open and closed. Research results. Females in the control group performed knee joint proprioception task better with an extended knee at velocity of 2°/s with open eyes during the follicular phase, but at the velocity of 10°/s the values were better during ovulation. Basketball players performed the same task better at velocity of 5°/s during ovulation, but at velocity of 10°/s the values were better during the luteal phase. Females in control group performed knee joint proprioception task with an extended knee at the velocity of 5°/s with closed eyes better during the luteal phase. No statistical difference between control group and basketball player indices of knee joint position proprioception task with a flexed knee at velocity of 2°/s, 5°/s and 10 °/s with closed eyes during the menstrual cycle was found. Discussion and conclusion. Knee joint proprioception indices were better during ovulation phase in control group and basketball players. Keywords: knee joint proprioception, follicular phase, ovulation, luteal phase.